Peer Acceptance Mahasiswa Non-Disabilitas Terhadap Mahasiswa Disabilitas pada Perguruan Tinggi di Sumatera Barat (Deskriptif Kuantitatif) - Najma Puspita Sari; Johandri Taufan; Setia Budi; Syari Yuliana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Studies on peer acceptance are important because peer acceptance is one of the factors that can influence the creation of social interactions and an inclusive educational environment for students with disabilities. This study aims to describe the peer acceptance of non-disabled students towards students with disabilities at Padang State University and Andalas University. This study uses a quantitative approach with a descriptive design. The research sample consisted of 100 non-disabled students selected using a purposive sampling technique, with 54 respondents from Padang State University and 46 respondents from Andalas University. Data were collected using a questionnaire and analyzed descriptively through the mean value, standard deviation, frequency, and percentage. The results showed that the level of peer acceptance of non-disabled students towards students with disabilities was in the high category with an average score of 103.96. This finding indicates that non-disabled students who became respondents in the study have a positive level of acceptance towards students with disabilities. Practically, the results of this study can be input for universities in strengthening an inclusive campus culture by increasing disability literacy and creating a learning environment that supports positive interactions between students.